E2F3 renders an immunosuppressive tumor microenvironment in nasopharyngeal carcinoma: Involvements of the transcription activation of PRC1 and BIRC5 - Qiang Wang; Qi Yu; Yueyang Liu (Immunity, Inflammation and Disease, 2023)
Abstract Background E2F transcription factors are well‐recognized oncogenic molecules, and their correlation with immune cell infiltration has recently been reported. This work studies the impacts and mechanism of E2F transcription factor 3 (E2F3) in the growth and tumor microenvironment (TME) of nasopharyngeal carcinoma (NPC). Methods Aberrantly expressed transcription factors in NPC were screened by abundant bioinformatics analyses. Gene expression in NPC cells was analyzed by reverse transcription‐quantitative polymerase chain reaction and Western blot analyses. Malignant behaviors of NPC cells were analyzed by cell counting kit‐8, 5‐ethynyl‐2′‐deoxyuridine labeling, Transwell assays, and xenograft tumor models. TPA‐induced THP‐1 cells (macrophages) were cultured in the conditioned medium of NPC cells to mimic tumor‐associated macrophages (TAMs) in vivo, and these TAMs were cocultured with CD8+ T cells. Regulation of E2F3 on protein regulator of cytokinesis 1 (PRC1) and baculoviral IAP repeat containing 5 (BIRC5) was validated by chromatin immunoprecipitation and luciferase reporter assays. Results E2F3 was highly expressed in NPC cells, and its knockdown suppressed malignant behavior and tumorigenic ability of the cells. The E2F3 knockdown condition downregulated M2 cytokines CD163 and interleukin‐10 in TAMs, which further enhanced proliferation and activation of the cocultured CD8+ T cells. E2F3 promoted transcription of PRC1 and BRIC5. Furthermore, PRC1 or BRIC5 upregulation in NPC cells restored the malignant properties of NPC cells, reprogrammed the TAMs to M2 phenotype, and suppressed the CD8+ T cell proliferation and activation. Conclusion This work suggests that E2F3 renders an immunosuppressive TME in NPC by activating PRC1 and BIRC5. Suppression of any member involved might favor tumor elimination.